PENGGUNAAN BUKU SAKU PRAKTIKUM KIMIA UNTUK MENINGKATKAN KERJA ILMIAH DAN KETERAMPILAN GENERIK - pakiz, Rudiyanto; Cahyono, Edy; Subroto, Tjahyo (Universitas Negeri Semarang, 2013)
The previous study that was conducted absolutely shown that the students of SMAN 1 Wonosari grade XI IPA have less practical ability related to the laboratorial aspects, so that material studies are surely needed in order to ease the students in practical work. The purpose of this research is to measure the influence of the usage of Buku Saku Praktikum Kimia as material studies toward scientific inquiry and generic skill in acid-basic chapter/study. The design of this research is using pre-test - post-test group. The method of the aggregation of data is using the documentation, test, observation, and questionnaire method. Based on the Normalized gain experiment , the result of logical inferention of generic skill for experiment group is 51,29% and the control group is 42,37%, generic skill’s direct observation of experiment group is 84,73% for the practical work I and 87,68% for the practical work II, control group is 74,97% for the practical work I and 80,32% for the practical work II and the scientific inquiry’s result for the experiment group I is 86,82 for the practical work I and 85,32 for the practical work II. Control group is 81,80 for the practical work I and 81,23 for the practical work II. The conclusions of this study is buku saku praktikum kimia work to develop scientific and generic skills of students in practical solution of the acid-base.